Revision of the Neotropical Xanthandrus Verral (Diptera, Syrphidae) - Zuleica M. Borges; Denise M. Pamplona (Revista Brasileira de Entomologia, 2003)
The Neotropical genus Xanthandrus Verral, 1901 is revised. Six species are redescribed: X. bucephalus (Wiedemann, 1830), X. cubanus Fluke, 1936, X. mellinoides (Macquart, 1846), X. mexicanus Curran, 1930, X. nitidulus Fluke, 1937, and X. plaumanni Fluke, 1937. Three species are included based on original descriptions: X. flavomaculatus Shannon, 1927, X. palliatus (Fluke, 1945), and X. simplex (Loew, 1861). New synonyms proposed: Argentinomyia longicornis (Walker, 1837) = Xanthandrus biguttatus Hull, 1945 syn. nov., and Xanthandrus bucephalus (Wiedemann, 1830) = Melanostoma quadrinotata Bigot, 1884 syn. nov. Description of terminalia, a key for Neotropical species, and illustrations are also presented.